2006
DOI: 10.1007/s10562-005-9614-4
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Reduction of Quinolines Catalyzed by Rhodium and Iridium Complexes with mono-, di-, and tri-dentated Phosphine Ligands

Abstract: The systems prepared in situ by addition of the corresponding equivalents of the respective phosphine (mono-, di-and tridentated), called M 2 Cl 2 (COE) 4 /n phosphine (M = Rh, Ir; and COE = cyclooctene), are efficient and regioselective precatalysts for the hydrogenation of quinoline, isoquinoline, 5,6-and 7,8-benzoquinoline and acridine. The Rh systems were more active than the corresponding Ir ones, being the systems with 1,1,1-tris(diphenylphosphinomethyl)ethane (triphos) more active than those with 1,2-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…It was believed that this dihydrido-iridium complex was generated by the initial formation of a bis(quinoline) complex, [Ir(Q) 2 (triphos)] ? , which dissociates a Q ligand and subsequently added dihydrogen to generate the corresponding dihidrido complex [14].…”
Section: The Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…It was believed that this dihydrido-iridium complex was generated by the initial formation of a bis(quinoline) complex, [Ir(Q) 2 (triphos)] ? , which dissociates a Q ligand and subsequently added dihydrogen to generate the corresponding dihidrido complex [14].…”
Section: The Reaction Mechanismmentioning
confidence: 99%
“…Recently, we report the hydrogenation of the heterocyclic ring of Q, as well as acridine and other benzoquinolines, catalyzed by the systems prepared in situ by addition of mono-, bi-and tridentated phosphine to M 2 Cl 2 (COE) 4 (M = Rh, Ir; COE = cyclooctene); for the Q hydrogenation, the more efficient system was Rh 2 Cl 2 (COE) 4 /2 triphos [14]. Continuing our work on kinetics and mechanisms of homogeneous catalytic reactions, in the present work we report kinetic and mechanistic studies of the reduction of Q to THQ by using the rhodium and iridium systems M 2 Cl 2 (COE) 4 /2 triphos as the precatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes M 2 (COE) 4 Cl 2 (M = Rh, Ir) were synthesized by a procedure published in the literature [17]. The reaction procedure is similar to those reported earlier [8,16]. The reaction was followed by measuring the hydrogen pressure drop as a function of time, and the composition of the solution was analyzed by means of a 610 Series UNICAM gas chromatograph fitted with a thermal conductivity detector and a 3 m 10% SE-30 on Supelcoport glass column using helium as carrier gas, which was coupled to a UNICAM 4815 data system.…”
Section: Methodsmentioning
confidence: 99%
“…So far the used precatalysts are based on monodentate phosphines, although systems containing tris(pyrazolyl)borate ligands have been also reported in the literature [15]. Recently, we reported the regioselective hydrogenation of the heteroaromatic ring of quinoline (Q), isoquinoline (iQ), 5,6-and 7,8-benzoquinoline (BQ) and acridine (A) catalyzed by rhodium and iridium systems containing mono-, bi-and tridentated phosphines (M 2 Cl 2 (COE) 4 /n phosphine); 1,2-bis(diphenylphosphino)ethane (dppe) was used as bidentated ligand [16]. Now, we report a comparative study of the use of rhodium and iridium diphosphine systems M 2 Cl 2 (COE) 4 /2 diphos, diphos = dppe, 1,3-bis(diphenylphosphino)propane (dppp) and 1,4-bis(diphenylphosphino) butane (dppb) in the hydrogenation of heteroaromatic nitrogen compounds.…”
Section: Introductionmentioning
confidence: 99%
“…(M = Rh, Ir; x = 2, y = 0 [7,8]; x = 1, y = 1 and x = 0, y = 2 [9]), [MH(CO)[NCMe) 2 (PPh 3 ) 2 ] ? (M = Ru, Os) [10,11], the systems RuCl 2 (NCMe) 4 /Tp and M 2 Cl 2 (COE) 4 /Tp (Tp = tris(pyrazolyl)borate ligands) [12] and more recently the systems prepared in situ by addition of mono-, bi-and tridentate phosphine to M 2 Cl 2 (COE) 4 (M = Rh, Ir; COE = cyclooctene) [13,14]; RuH 2 (g 2 -H 2 ) 2 (PCy 3 ) 2 has been the only precatalyst reported that hydrogenates the nonheterocyclic ring of Q [15]. Recently, we reported a kinetic and mechanistic studies of the reduction of Q catalyzed by M 2 Cl 2 (COE) 4 /2 triphos systems (M = Rh, Ir) [16].…”
Section: Introductionmentioning
confidence: 99%